Politik Islam, Demokrasi, “Kepekaan Gender”, dan Feminisme - Qamar, Subaidi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2008)
Democratic system was estableshed in the Athena,without there is not equality of righs by womens. She is thesecond class and have not Franchise. But the Moderndemocratics system in American government was practically onequelity of righs, freedom of consience,freedom ofopinion,freedom of expression, and economic freedom. And arealistic, democratic and responseble government wasestableshed by the prophet of Islam. As many as fourteencentury before this time. Equelity of righs, independence ofopinion and freedom expreesion, werw all cultivated with aview to developping a sound nation caracter, it is nore wotheythat this way succes fully achieved and carnet out in practice inthe teeth on two adverse factors. One of them was the fact ofthe prophet receiving revelition for guidance of the people. Hecould very well play the roll of shepherd, driving the sheep inthe direction liked; but the case, he could not become a nationbuilden nor a democrat.